(untitled) (International journal of medical sciences, 2025)
This article examines the advantages, procedural stages, and clinical effectiveness of laparoscopic endosurgical techniques in repairing abdominal wall diastasis during abdominoplasty. The results show that laparoscopic plication (endosuturing) is less traumatic than conventional open abdominoplasty, with reduced blood loss, milder pain, and shorter rehabilitation time. The laparoscopic technique also improves cosmetic outcomes and enhances patients’ quality of life.